Madrassa Diniyah Curriculum Transformation In Pesantren: A Study Of Wali Songo Mimbaan And Salafiyah Syafi’iyah Sukorejo Pesantren In Situbondo - Sulaiman, Sulaiman; Halim Soebahar, Abd; Mundir, Mundir (International Journal of Educational Research & Social Sciences, 2023)
The transformation in pesantren has had many challenges over time because the center to spread Islamic religion and Islamic education is pesantren. The existence of pesantren has been present and has experienced developments starting from the early days of Islam entering Indonesia. Curriculum development can be based on reforms in certain fields. For example, the discovery of new learning theories and changes in society's demands on schools. So that the curriculum is expected to be able to build certain developments, as a result of advances in science and technology and technology information, as well as globalization, history, differences in student backgrounds, society philosophical values, religion, certain groups, and cultural ethnicities. The research focuses are: 1) what is the objective transformation of the Madrassa Wustha curriculum at Wali Songo Mimbaan Situbondo and Salafiyah Syafi'iyah Sukorejo pesantren in Situbondo? 2) how is the transformation of Madrassa Wustha curriculum contents at Wali Songo Mimbaan Situbondo and Salafiyah Syafi'iyah Sukorejo  Pesantren in Situbondo?  3) how is the transformation of the Madrassa Diniyah Wustha curriculum method at Wali Songo Mimbaan Situbondo and Salafiyah Syafi'iyah Sukorejo  Pesantren in Situbondo? This research implements a qualitative approach with a multi-site study type of research. The determination of research subjects was carried out purposively. The data sources use primary data and secondary data. Data collection techniques using participatory observation, in-depth interviews, and documentation studies. Data analysis uses descriptive qualitative with an interactive model by Miles and Huberman. Data validity uses source triangulation and method triangulation.